Shiny objects - Benedict, Dianne, 1941- (Iowa School of Letters award for short fiction., 1982)
A successful professional painter and art instructor for years, Benedict was dissatisfied that she could paint petal-perfect flowers and expensive portraits of wealthy clients, but could not capture the light on the garden at dusk or the tender hands and faces of her own children. Seven years ago she walked into a poetry workshop and found "the window I needed for my imagination." She never painted another painting, and has never stopped writing. She got her BA in English and her MFA in writing at Goddard College